SURVEI TERHADAP GURU SEKOLAH DASAR: KESIAPAN MENGINTEGRASIKAN STEM DALAM PEMBELAJARAN DI KOTA KUPANG - Marlispin, Agustiana; Yandita , Caesilia; Boytekan, Ester; Boimau, Esteriani; Lola, Falentina; Apolinselmi, Geronsa; Maxel Koroh; Kurniayu Triastuti R. A. Ratu8 (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to obtain an overview of the readiness of elementary school teachers in integrating STEM into learning in Kupang City. The study used a quantitative descriptive method by distributing questionnaires to 110 respondents, which were analyzed using a four-point Likert scale. The results show that all readiness indicators are in the good category, with the following mean values: knowledge and understanding of STEM at 2.92, attitude towards STEM integration at 2.57, teacher self-efficacy at 2.80, and school environment support at 2.69. These findings indicate that teachers have an adequate understanding of the concepts and benefits of STEM, although they still experience difficulties in applying the technology and engineering components due to limited practical training and learning resources. Teachers' attitudes tend to be positive but are still accompanied by doubts regarding the perceived complexity of implementing STEM in schools with minimal facilities. Teachers' self-efficacy is relatively good, but some still need assistance in developing systematic STEM teaching modules. School support is considered adequate but not yet optimal, especially in terms of providing learning tools and access to training. Overall, the results show that elementary school teachers in Kupang City are well prepared to integrate STEM. However, strengthening institutional support and increasing practice-based training are still needed to ensure effective and sustainable implementation.